Diabetes does not influence activation of coagulation, fibrinolysis or anticoagulant pathways in Gram-negative sepsis (melioidosis) - Koh, Gavin C. K. W; Meijers, Joost C. M.; Maude, Rapeephan R.; Limmathurotsakul, Direk; Day, Nicholas P. J.; Peacock, Sharon J.; Poll, Tom van der; Wiersinga, Willem J. (Thrombosis and Haemostasis, 2011)
Diabetes is associated with a disturbance of the haemostatic balance and is an important risk factor for sepsis, but the influence of diabetes on the pathogenesis of sepsis remains unclear. Melioidosis (Burkholderia pseudomallei infection) is a common cause of community-acquired sepsis in Southeast Asia and northern Australia. We sought to investigate the impact of pre-existing diabetes on the coagulation and fibrinolytic systems during sepsis caused by B. pseudomallei. We recruited a cohort of 44 patients (34 with diabetes and 10 without diabetes) with culture-proven melioidosis. Diabetes was defined as a pre-admission diagnosis of diabetes or an HbA1c>7.8% at enrolment. Thirty healthy blood donors and 52 otherwise healthy diabetes patients served as controls. Citrated plasma was collected from all subjects; additionally in melioidosis patients follow-up specimens were collected seven and ≥28 days after enrolment where possible. Relative to uninfected healthy controls, diabetes per se (i.e. in the absence of infection) was Characterised by a procoagulant effect. Melioidosis was associated with activation of coagulation (thrombin-antithrombin complexes (TAT), prothrombin fragment F1+2 and fibrinogen concentrations were elevated; PT and PTT prolonged), suppression of anti-coagulation (antithrombin, protein C, total and free protein S levels were depressed) and abnormalities of fibrinolysis (D-dimer and plasmin-antiplasmin complex [PAP] were elevated). Remarkably, none of these haemostatic alterations were influenced by pre-existing diabetes. In conclusion, although diabetes is associated with multiple abnormalities of coagulation, anticoagulation and fibrinolysis, these changes are not detectable when superimposed on the background of larger abnormalities attributable to B. pseudomallei sepsis.
Keywords: Diabetes mellitus; Burkholderia pseudomallei; melioidosis; coagulation; fibrinolysis